Cr(vi) removal by combined redox reactions and adsorption using pectin-stabilized nanoscale zero-valent iron for simulated chromium contaminated water. Issue 80 (2nd September 2015) - Chen, Dan; Yang, Kai; Wang, Hongyu; Zhou, Jun; Zhang, Huining
<x xml:space="preserve">Abstract</x> Pectin-stabilized nanoscale zero-valent iron was used to removal Cr(vi) and the main mechanisms were redox reaction and adsorption.